Effect of AIUEO Vocal Therapy in Non-Hemorrhagic Stroke Patients with Verbal Communication Disorders: A Case Report - Intan Nur Annisa; Rondhianto; Ana Nistiandani; Mohammad Shodikin (Health and Technology Journal (HTechJ), 2024)
Stroke is a disease that is a health problem throughout the world. Stroke can cause long-term damage to nerve function or brain damage, long-term disability, and even death. Stroke can cause sufferers to experience weakness due to damage to nerve function. If a stroke attacks the left brain and hits the speech center, it is likely that the patient will experience speech disorders or verbal communication disorders. One form of rehabilitation therapy to correct verbal communication disorders in someone who suffers from verbal communication disorders is "AIUEO" vocal therapy. The aim of this research is to obtain an overview of AIUEO vocal therapy for verbal communication disorders in non-hemorrhagic stroke patients. The method used is to collect the results of the analysis of the patient's verbal communication disorders on the first, second and third days after being given AIUEO vocal therapy using SOP and the Frenchay Aphasia Screening Test (FAST) instrument. The results obtained during the three days of implementation were that patients experienced an increase in verbal communication skills from an initial FAST score of 12 (severe category) to 19 (moderate category). The conclusion of this research is that giving AIUEO vocal therapy can reduce the score of verbal communication disorders in patients, can overcome the weakness of speech muscles in stroke patients, and can stimulate improvement in language skills in stroke patients.